1971
DOI: 10.1039/tf9716702989
|View full text |Cite
|
Sign up to set email alerts
|

?-Radiolysis of gaseous H2S + SF6 mixtures

Abstract: Measurement of G(ion) (= 1 0 0 / W ~) and G(H& in H2S+SF6 mixtures, where WM is the average energy required to produce an ion pair in the mixture, and G(ion) and G(H~)M are the total ion yield and hydrogen yield respectively, enables energy partition parameters a to be calculated. These were found to be a = 1.44 for mixtures of stopping power fraction 2 = P1/(Pl+S2P2/Sl), (where P and S refer to pressure and stopping power of gases 1 and 2) between -h 0.2 and 1 .O. Below 2 -I I . 0.2 each mixture has its own p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1973
1973
1976
1976

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Rcently several studies of the radiolysis of hydrogen sulfide have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and we have proposed a mechanism based on our measurements at high dose rates (13). While this mechanism is in general agreement with the observed yields there are problems which need further investigation.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Rcently several studies of the radiolysis of hydrogen sulfide have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and we have proposed a mechanism based on our measurements at high dose rates (13). While this mechanism is in general agreement with the observed yields there are problems which need further investigation.…”
Section: Introductionsupporting
confidence: 75%
“…At high dose rates for single pulse irradiations in pure H,S, charge neutralization involves the free electron, reaction 1 . 3 On the addition of SF,, SF6-is involved in the neutralization step and the formation of hydrogen atoms, [I], is suppressed.…”
Section: Introductionmentioning
confidence: 99%